Effect of Adding Palm Kernel Cake as a Substrate in Sclerotium rolfsii Inoculum - Kadran Fajrona; Yose Rizal; Mirnawati (Andalasian Livestock, 2024)
This research aims to determine the added palm kernel cake (PKC) level in the Sclerotium rolfsii inoculum. This research used an experimental method with a completely randomized design, four treatments, and five replications. The treatments were different substrate compositions, consisting of 100% bran (control), 90% bran + 10% PKC (P1), 85% bran + 15% PKC (P2), and 80% bran + 20% PKC (P3). The variables observed were cellulase and mannanase enzyme activities. The data obtained were analyzed statistically using a completely random design analysis of variance and continued with Duncan's multiple range tests if the treatment influenced the observed variables. The results showed that adding PKC as a substrate in making Sclerotium rolfsii inoculum had a significant effect (P<0.01) on the activity of cellulase and mannanase enzymes. The best cellulase and mannanase enzyme activities were found in the 80% fine bran substrate composition + 20% PKC (P3), namely 16.02 U/mL and 7.81 U/mL.